The spirit of Shinto mythology - Mason, J. W. T. (Fuzambo, 1939)
This book introduce creative spirit in Shinto, history and heaven, death in Shinto, purification and evil, symbolism and personality, heaven not omnipotent, ara-mitama and nigi-mitama, divine spirit makes th land...